Feasibility Study of Carbon Pelletizing Plant for use in ferrosilicon Production - Jónas Þór Markússon 1989- (2016)
This thesis looks into the financial feasibility of pelletizing carbon-rich raw material for the production of ferrosilicon and is done in co-operation with Elkem Iceland which runs a ferrosilicon foundry located in Iceland. The feasibility of changing the conventional raw material with lower grade pelletized material will be analysed. This is done in the hope of cutting down production cost and improving the production process. A preliminary design of a pelletizing plant is described where all major production equipment is listed along with their cost. The financial performance of this plant is reviewed. Five different pelletizing production cases are reviewed; they differ in the amount of conventional raw material replaced. The amount of conventional raw material replaces grows from 42% in the smallest case and up to 100% of the annual consumption. The results of this analysis are that pelletizing is profitable for all five production cases. A sensitivity analysis is performed which serves as a base for further valuation. Elkem Iceland